The Role The Family Plays In Psychological Support For The Recovered From Corona - Talah, Nacera (جامعة الوادي - University of Eloued, 2022)
the current theme is looking for more information about the importance of the psychological homely support and its role to reduce the Corona sufferer's pain and suffering , because the person who has the support from their family members becomes somebody who has self estimate and confidence, less exposed to the disadvantages because of the illness and the period they come through, becomes also stronger to go through it and fight the disease, so we find that homely psychological support strengthens the patient and reduces the reduces the psychological pain. الملخص: يحاول الموضوع الحالي التعرف على اهمية التكفل النفسي الاسري ودوره في في كيفية التخفيف من معاناة ان المريض المتعافى من الكورونا ، لان الفرد الذي يتمتع بالتكفل من افراد اسرته يصبح شخصا واثقا من نفسه ، واقل عرضة للآثار النفسية نتيجة المرض الذي مر به ، واكثر قدرة على المقاومة والتغلب على كل ذلك، لذلك نجد ان التكفل النفسي الاسري يزيد من قدرة الفرد على مقاومة اثار المرض، وتقلل الكثير من المعاناة النفسية
دور الاسرة في التكفل النفسي بالمريض المتعافى من الكورونا
article
Keywords: the psychological homely support , the family , Corona virus